Assessment of "Cuti-Cuti Malaysia" as an Advertising Campaign Among Residents in Peninsular Malaysia - Ibrahim, Norhizaliney (2006)
The tourism industry in Malaysia is the second largest contributor to the country's economy. The parties involved, especially Ministry of Tourism Malaysia, is making great efforts to promote tourism destinations in the country to local and foreign tourists. One of the programs that had been organized was the "Cuti-cuti Malaysia" or "Malaysia Holiday" campaign that was designed to encourage Malaysians to go for holidays locally. In order to determine the success of the program, a study has to be conducted to obtain feedbacks from the public regarding the advertisements viewed or heard. Thus, this study was conducted to assess the effectiveness of the advertisements "Cuti-cuti Malaysia" while promoting the tourism destinations in Malaysia. The Hybrid model, which is the combination between the 'Tracking' and 'Conversion' techniques, was used as a basic and guideline in this study. Sampling for the sample population was conducted to 400 Telekom Malaysia's fixed-line their customers using a 'Random Digit Dialing' method from the Telekom Malaysia's phone directory. The area of study covered Peninsular Malaysia which was divided into four divisions which are the East coast region (Terengganu, Kelantan and Pahang), Northern (Perak), Southern (Negeri Sembilan and Melaka) and Central region (Selangor, Kuala Lumpur and Putrajaya). The Descriptive analysis, Reability analysis, ANOVA, T-test and Crosstab subprogram from SPSS were used to analyze the data. From the result, it could be concluded that the campaign was a success but the local public awareness towards the advertisements on the "Cuti-cuti Malaysia" campaign was not encouraging. This is because only 66 percent had agreed to go for a holiday aRer viewing or hearing the advertisements. Besides that, most local tourists were not interested to seek the services of the tourism agency in their plans for holidays. In the aspect of the advertisement's message, 69 percent could not recall the theme for a certain advertisement that was watched or heard, but they could remember the singer of its jingles, the slogan "Cuti-cuti Malaysia", the images and graphics and also some information. The television, newspapers, radio, magazines and posters were the medium that had the most percentage of audiences compared to tourism articles, billboards, brochures, cinemas, the Internet and telephone. All of results obtained in this study are to provide some insights that can be useful in the fbture for planning and marketing of local tourism destination to the public.